The rise and fall of paper money in Yuan China, 1260–1368 - Guan, Hanhui (2024)
Following the Mongol invasion of China, the Yuan (1260–1368) dynasty was the first political regime to introduce a precious metal standard and deploy paper money as the sole legal tender. Drawing on a new dataset on money issues, prices, warfare, imperial grants, taxation, natural disasters, and population, we find that a silver standard initially consolidated the Chinese currency market. However, persistent fiscal pressures eventually compelled rulers to ease the monetary standard, and a fiat standard was adopted. We show that inflation was high in the early and late periods of the dynasty but remained moderate for nearly half a century. We find that military pressure, particularly civil war, generated fiscal demands that led to the over-issuance of money. By contrast, natural disasters and imperial grants did not trigger the over-issue of money. Warfare was much more likely to increase paper money issues under the fiat standard than during the silver standard period.